Dietary glucose oxidase and/or catalase supplementation alleviates intestinal oxidative stress induced by diquat in weaned piglets. (3rd October 2021) - Sun, Xiaojiao; Piao, Longguo; Jin, Haifeng; Nogoy, Kim Margarette C.; Zhang, Junfang; Sun, Bin; Jin, Yi; Lee, Dong Hoon; Choi, Seongho; Li, Xiangzi
Abstract: This study investigated the effects of dietary exogenous glucose oxidase (GOD) and/or catalase (CAT) on the intestinal antioxidant capacity and barrier function in piglets under oxidative stress. Sixty pigs assigned randomly to five treatment groups—CON: basal diet; DIQ: basal diet; GOD: basal diet + 40‐U GOD/kg diet; CAT: basal diet + 50‐U CAT/kg diet; and GC: basal diet + 40‐U GOD/kg diet + 50‐U CAT/kg diet—were analyzed. On Day 14, the CON group was injected with saline, and the others were treated with diquat. The results showed that in diquat‐treated piglets, supplementation of dietary GOD and CAT elevated the superoxide dismutase and CAT activities and attenuated the malondialdehyde level in plasma and intestinal mucosa, enhanced the duodenal villus height and villus height/crypt depth ratio, upregulated ZO‐1 mRNA level, and attenuated the apoptosis of the epithelial cells and caspase‐3 mRNA level in the intestine. Additionally, the supplementation upregulated mRNA expression of the intestinal NF‐E2‐related factor 2‐regulated genes in diquat‐treated piglets. However, GOD combined with CAT could not alleviate oxidative damage better than supplementation of CAT or GOD alone under oxidative stress. Overall, the study provides a potential alternative that could relieve the weaning stress in piglets and help formulate antibiotic‐free diets.